Portrayal of Qawwali in Asian Cinema: Comparative Analysis of Bollywood and Lollywood Movies (The Journal of Cultural Perspectives, 2023)
This research consists of examining Qawwali in Bollywood and Lollywood movies. Research studies the evolutionary journey of Qawwali in Bollywood and Lollywood and examines the similarities and differences in the presentation of Qawwali in these two cinemas. For this purpose, Qawwalis have been taken from both the cinemas. The formed frames and their sub-indicators have been analyzed by the method of content analysis and it has been observed since then what changes have taken place at the level of presentation, poetry and musical instruments in Qawwali. Meaning theory of media portrayal is integrated with the research. After examining the frames and their respective indicators from the Qawwalis of the both cinema, the research concludes that Indian movies continue to inculcate the music genre Qawwali, while Pakistani movies do not, due to a lack of priorities, cultural reluctance and innovation in the industry